Behavioral Effects and Retention of Protein Immunomarkers on Plum Curculio Conotrachelus nenuphar (Coleoptera: Curculionidae). Issue 6 (6th November 2021) - Lampasona, Timothy; Acebes-Doria, Angelita; Leskey, Tracy C; Nielsen, Anne L
Abstract: Protein immunomarking can be used to track the dispersal of insects in the field or identify plant–insect interactions. By marking insects with known proteins and recapturing them, their movement or host use can be quantified with Enzyme Linked Immunosorbent Assay (ELISA). Before using this technique, retention and behavioral effects of these markers should be evaluated to ensure that the insect's natural behaviors are conserved. Here, we tested the effects of protein markers on the plum curculio, Conotrachelus nenuphar (Coleoptera: Curculionidae) using two different application methods. This weevil is native to North American and a pest of tree fruit and blueberry in the United States and causes damage resulting in near complete crop loss if left untreated. We tested the effects of marking adult C. nenuphar with two inexpensive food-based immunoprotein markers, bovine casein (cow's milk) and chicken albumin (egg whites) on climbing distance (total cm), lateral movement (total cm), and lateral movement speed (cm/s), as well as retention time of protein immunomarkers. Neither protein immunomarker affected C. nenuphar movement or climbing, although females climbed significantly greater distances than males. ELISA assays detected 37.5–56.2% of milk protein and 56.2–59.3% of egg on the insect 7 d after application depending on application method. Our findings indicate that food-based protein immunomarkers can be used in future studies to test C. nenuphar movement within host plants without impacting behavior. The use of protein immunomarking will allow studies that will lead to behaviorally based management tactics.